Վազգէն Ա. Ամենայն Հայոց Կաթողիկոսի գործունէութիւնը նորայայտ փաստաթղթերի համաձայն (1958—1989) - Հարությունյան, Ավագ Ա. (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Католикос всех армян Вазген Первый возглавил Армянскую Апостольскую Церковь в судьбоносный и исторически значимый период, как для армянского народа, так и для самой Церкви. Настоящая публикация включает ряд документов, отражающих ключевые аспекты его деятельности, в частности: — издательские и полиграфические вопросы (разрешения на издание Евангелия, проповедей, альбомов о Св. Эчмиадзине, публикации отчетов о зарубежных визитах), — официальные разрешения на проведение юбилеев (дня рождения, интронизации), благословения мира и созыв архиерейских соборов, — визиты Вазгена Первого за рубеж и прием иностранных делегаций в Св. Эчмиадзине, — решения руководящих органов (ЦК КП Армении, Верховного Совета СССР и Армянской ССР) о его награждении. Все документы снабжены необходимыми комментариями, позволяющими современному читателю глубже понять политику коммунистического режима в отношении Церкви. Публикуемые материалы — ранее неизвестные и впервые вводятся в научный оборот. Большинство из них переведены с русского языка. Это архивные документы ЦК КП Армении, Совета Министров Армянской ССР и Совета по делам Армянской церкви. Часть из них имеет гриф «Особая папка», присваиваемый особо важным и секретным решениям. Catholicos of All Armenians Vasken I assumed the leadership of the Armenian Apostolic Church during a critical and historically significant period for both the Armenian nation and the Church. This publication presents a series of archival documents that shed light on the key aspects of his activities, including: — Publishing and printing matters (approvals for the publication of the Gospel, Vasken I’s sermons, albums on Holy Etchmiadzin, and reports on his foreign visits), — Permissions to celebrate jubilees (birth and enthronement anniversaries), perform the blessing of the Holy Chrism (Myron), and convene episcopal assemblies, — Authorizations for Vasken I’s official visits abroad and the reception of foreign delegations in Holy Etchmiadzin, — Decisions by the Central Committee of the Communist Party of Armenia, the Supreme Soviet of the USSR, and the Armenian SSR concerning his awards and honors. All documents are accompanied by explanatory notes, allowing the modern reader to better understand the Soviet government’s policy toward the Church. The published materials are being introduced into scientific circulation for the first time. Most of them have been translated from Russian. These are archival documents of the Central Committee of the Communist Party of Armenia, the Council of Ministers of the Armenian SSR, and the Council for Religious Affairs. Some of them are marked “Special Folder,” a designation given to particularly important and secret decisions.
Keywords: Պատմութիւն; Վազգէն Ա. Ամենայն Հայոց Կաթողիկոս; Հայ եկեղեցւոյ գործիչներ